Anti-inflammatory function of arctiin by inhibiting COX-2 expression via NF-κB pathways - Lee Chong-Kil; Kwak Jin-Hwan; Kwon Jeunghak; Kim Kwanghee; Han Shinha; Kim Hyunyul; Shin Seulmee; Lee Sungwon; Ha Nam-Joo; Yim Dongsool; Kim Kyungjae (BMC, 2011)
Abstract Background Arctiin, isolated from Forsythia suspensa has been reported to have anti-inflammatory, anti-oxidant, antibacterial, and antiviral effects in vitro. However, there has been a lack of studies regarding its effects on immunological activity. The aim of this study is to investigate the anti-inflammatory potential and possible mechanisms of arctiin in LPS-induced macrophages. Methods We investigated the mRNA and protein levels of proinflammatory cytokines through RT-PCR and western blot analysis, followed by a FACS analysis for surface molecule changes. Results Arctiin dose dependently decreased the production of NO and proinflammatory cytokines such as IL-1β, IL-6, TNF-α, and PGE2, and it reduced the gene and protein levels as determined by RT-PCR and western blot analysis, respectively. The expression of co-stimulatory molecules such as B7-1 and B7-2 were also inhibited by arctiin. Furthermore, the activation of the nuclear transcription factor, NF-κB in macrophages was inhibited by arctiin. Conclusion Taken together these results provide evidence of the bioactivity of arctiin in inflammatory diseases and suggest that arctiin may exert anti-inflammatory effect by inhibiting the pro-inflammatory mediators through the inactivation of NF-kB.